Macroevolution and adaptive processes of the Leptocoeliidae family (Brachiopoda) throughout the Silurian and Devonian (Terr@ Plural, 2023)
The Leptocoeliidae family (genera Anabaia, Australocoelia, Eocoelia, Leptocoelia, Leptocoelina and Pacificocoelia) has an  important place in the global paleobiogeography, during the Silurian and Devonian. During these periods, global  climate changes impacted a lot of invertebrate faunas in the epicontinental seas of Gondwana. In the Silurian, the genus  Eocoelia reached a cosmopolitan behavior, while Leptocoelia emerged by adaptive sympatric processes and Anabaia became extinct. After that, during the Devonian, the genus  Australocoelia emerged and reached cosmopolitan levels while Leptocoelina and Pacificocoelia emerged by sympatries in  the equatorial regions. Australocoelia, during the  Devonian, occupied the same ecological niches that were  previously occupied by Anabaia in the Silurian. It can be said that the same occurred with Pacificocoelia and Eocoloelia in  the seas of Laurentia, configuring a process of succession  of faunas.
Keywords: succession of faunas; paleobiogeography; Gondwana; climate change